2021
DOI: 10.1590/1676-0611-bn-2021-1207
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of the ichthyofauna of Mamirauá Sustainable Development Reserve, Middle Solimões, Amazonas, Brazil: high richness in a large protected area of Western-Central Amazonia

Abstract: The present study reviews the records of occurrences of fish species found in the Mamirauá Sustainable Development Reserve (MSDR). The reserve is located in a large section of the middle Solimões River basin, in its interflow with Japurá River. For the elaboration of the list of fish species occurring in Mamirauá Reserve, we used a database of different studies on fish communities carried out in the area over the last three decades, in addition to the material deposited in the ichthyological collections of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…37 Many of them occur in the water bodies of the MSDR. 38,39 Thus, the concentrations of heavy metals in the milk of female Amazon river dolphin in this study may be a consequence of the metals transferred via food and bioaccumulation during the lactation period, which can last, on average, 2.8 years in Inia geoffrensis. 40 Martin and da Silva 41 showed that the Amazon river dolphin promotes habitat segregation, in which female dolphins and their calves are predominant in remote areas of the floodplains known as chavascais, while male dolphins are predominant in the main channels of the river.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…37 Many of them occur in the water bodies of the MSDR. 38,39 Thus, the concentrations of heavy metals in the milk of female Amazon river dolphin in this study may be a consequence of the metals transferred via food and bioaccumulation during the lactation period, which can last, on average, 2.8 years in Inia geoffrensis. 40 Martin and da Silva 41 showed that the Amazon river dolphin promotes habitat segregation, in which female dolphins and their calves are predominant in remote areas of the floodplains known as chavascais, while male dolphins are predominant in the main channels of the river.…”
Section: Resultsmentioning
confidence: 77%
“…The Amazon river dolphin is a top predator that consumes at least 43 fish species from 19 different families 37 . Many of them occur in the water bodies of the MSDR 38,39 . Thus, the concentrations of heavy metals in the milk of female Amazon river dolphin in this study may be a consequence of the metals transferred via food and bioaccumulation during the lactation period, which can last, on average, 2.8 years in Inia geoffrensis 40…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations